Similarities and differences of main left wing parties in Poland and Hungary: The case of SLD and MSzP in comparative perspective (1989—2014) - Kubas, Sebastian (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: The article presents Polish and Hungarian main left‑wing parties in the period of political transformation. There are a few sections in the article that develop the research problem: the genesis and development of the parties from 1989 to 2014, a comparative analysis of the two parties based on quantitative indices. One can say there are some similarities between SLD and MSzP. The parties were transformed from communist hegemon formations, then participated in free parliamentary elections with some successes, created several governments and both have recently faced considerable loss of support. SLD and MSzP belong to the parties that influenced Polish and Hungarian transformation greatly. Key words: political parties, Poland, Hungary, SLD, MSzP